PENGARUH KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI SMK PGRI 1 SALATIGA - Christwin Gideon Wehantouw; Tritjahjo Danny Soesilo; Yustinus Windrawanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of learning independence on the academic achievement of eleventh-grade students at SMK PGRI 1 Salatiga. Learning independence is considered an important internal factor that supports students in managing their learning process effectively, including regulating learning strategies, managing time efficiently, and taking responsibility for academic tasks. This research employed a quantitative approach using a simple linear regression design. The population consisted of all eleventh-grade students of SMK PGRI 1 Salatiga in the 2024/2025 academic year totaling 30 students, and the sampling technique used was total sampling, meaning that all members of the population were included as research participants. Data on learning independence were collected using a questionnaire, while academic achievement data were obtained from students’ academic scores documented by the school. The results of the study indicate that learning independence has a significant positive effect on students’ academic achievement, with a significance value of 0.003 (p < 0.05). The coefficient of determination shows that learning independence contributes 26.6% to students’ academic achievement, while the remaining 73.4% is influenced by other factors outside the scope of this study. These findings indicate that students with higher levels of learning independence tend to achieve better academic performance, therefore teachers and schools need to encourage the development of students’ learning independence to improve academic success.